2010
DOI: 10.1074/jbc.m109.066597
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Trypanosoma brucei p22 Protein, a Cytochrome Oxidase Subunit II-specific RNA-editing Accessory Factor

Abstract: Kinetoplastid RNA (k-RNA) editing is a complex process in the mitochondria of kinetoplastid protozoa, including Trypanosoma brucei, that involves the guide RNA-directed insertion and deletion of uridines from precursor-mRNAs to produce mature, translatable mRNAs. k-RNA editing is performed by multiprotein complexes called editosomes. Additional non-editosome components termed k-RNA-editing accessory factors affect the extent of editing of specific RNAs or classes of RNAs. The T. brucei p22 protein was identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 92 publications
0
26
0
Order By: Relevance
“…The p22 protein with the z64-kDa MBP-tag migrates as a band just below the BSA band, which served as a negative control because it does not bind RNA (Fig. 2, lanes 4,6; Sprehe et al 2010). TbRGG2-GST acted as a positive control for RNA binding ).…”
Section: Resultsmentioning
confidence: 99%
“…The p22 protein with the z64-kDa MBP-tag migrates as a band just below the BSA band, which served as a negative control because it does not bind RNA (Fig. 2, lanes 4,6; Sprehe et al 2010). TbRGG2-GST acted as a positive control for RNA binding ).…”
Section: Resultsmentioning
confidence: 99%
“…The P22–RBP16 interaction seems to be unstable or occurring with only a limited amount of P22 molecules, as it cannot be obtained by in vivo immunoprecipitation (Sprehe et al ., ). However, TbRGG2, an RNA‐editing factor from T. brucei , can be indeed immunoprecipitated (Sprehe et al ., ), suggesting P22 interacts with many different factors in vivo . In T. brucei , these interactions seem to be important for k‐RNA editing, primarily as a COII‐specific editing factor (Sprehe et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…2B). Mam33 family proteins have been identified in several organisms, which include T. brucei P22 and human P32 (Jiang et al, 1999;Hayman et al, 2001;Sprehe et al, 2010). All these proteins share structural topology and have thus been designated as orthologous proteins (Sprehe et al, 2010).…”
Section: A Screening For Modulators Of Tcubp1 Rna-binding Identifies mentioning
confidence: 99%
“…Additionally, simultaneous depletion of RBP16 and MRP1/2 revealed that these proteins have a redundant function in the maintenance of edited A6 (ATPase subunit 6) and cytochrome oxidase subunit III (COIII) RNAs (14). Depletion of the p22 protein resulted in a specific defect in editing of the COII RNA (15). The MERS1 (mitochondrial edited mRNA stability) Nudix hydrolase and TbRGG1 exhibit more global effects.…”
mentioning
confidence: 99%
“…The enzymes that catalyze editing, including endonucleolytic cleavage, uridine (U) addition or U removal, and the final resealing by ligation, are found in a stable multiprotein structure termed the RNA editing core complex (RECC) or 20S editosome (8-11). In addition, several noneditosome proteins facilitate the editing of one or more mRNAs in vivo (12)(13)(14)(15)(16). More recently, a large, dynamic macromolecular complex, termed the mitochondrial RNA binding 1 (MRB1) complex, otherwise known as RESC (RNA editing substrate binding complex [17]), has emerged as essential for mitochondrial RNA editing (4).…”
mentioning
confidence: 99%